Bouncing back queer resilience in twentieth and twenty-first century English literature and culture - Jung, Susanne 1975- (Queer studies, 2020)
LGBTQ people have strategies of resilience at their disposal to help them deal with the challenge that heteronormativity as a power structure poses to their affective lives. This book makes the concept of resilience available to queer literary and cultural studies, analysing these strategies in terms of narration, performance, bodies, and space. Resilience turns out to be a highly interactive mode of being in the world, which can set free creative energy as well as draw inspiration and energy from artistic work. Authors and artists discussed include Katherine Mansfield, Christopher Isherwood, Sylvia Townsend Warner, Jeanette Winterson, Michael Cunningham, and Ian McKellen